Perkembangan Pemasaran Home Industri Krupuk Seblak dan Mie Seblak melalui Instagram dan Whatsapp di Kelurahan Patokan Kecamatan Kraksaan Kabupaten Probolinggo - Alvan Fathony; Siti Rokaiyah; Sofiyatul Mukarromah; Saida Salsabila; Fitriyah Fitriyah; Vina Yuli Habsari; Riza Nur Aini; Dewi Susilowati; Laili Fauziah Aziz (Universitas Nurul Jadid, 2021)
The current development of Information and Communication Technology has had a huge impact on all aspects of life, including business and education. Technology has become a reliable strategy in a business. Business actors usually use technology for various things. Able to get information, share information, as a means of communication between business actors, as a place to buy and sell, and so on. The purpose of this research is to identify various online marketing models through Instagram and Whatsapp in the development of home industry products in Kraksaan Probolinggo. Identification of the types of products, tools, materials and processing methods is carried out through surveys, assistance and documentation. The results of product development and online marketing that the team focused on were 2 processed variations, namely seblak chips and seblak noodles. Marketing through Instagram and Whatsapp is very helpful in spreading products and sales can increase. Activities that have been carried out are in the form of improving product quality, increasing added value, using packaging, and labeling the product. And how to market via Instagram and Whatsapp. Based on observations, the public has gained knowledge and technology related to promotional techniques through Instagram and Whatsapp